Number–size distribution of aerosol particles and new particle formation events in tropical and subtropical Pacific Oceans. (October 2016) - Ueda, S.; Miura, K.; Kawata, R.; Furutani, H.; Uematsu, M.; Omori, Y.; Tanimoto, H.
Abstract: Number–size distributions of aerosol particles with diameters of 10–500 nm in the marine boundary layer were observed continually onboard the R/V Hakuho Maru over the equatorial and subtropical North Pacific and South Pacific during December 2011–March 2012. Number–size distributions over each area were parameterized using a sum of up to three lognormal functions. Bi-modal size distributions with peak diameters at 30–80 nm (Aitken mode) and 100–200 nm (accumulation mode) were observed frequently. Larger peak diameters of Aitken and accumulation modes were observed over the eastern equator, where 5-day backward trajectories showed that the air masses had derived from high-chlorophyll oceanic regions without precipitation. Smaller peak diameters and low concentrations were often observed over the North Pacific. The trajectories show that such air mass originated from oceanic regions with less chlorophyll, exhibiting high precipitation frequency. New particle formation (NPF) events have often been observed over the mid-latitude eastern South Pacific with a low condensation sink (CS) and some dimethyl sulfide, although none was observed over the equator, where CS was higher. The lesser CS condition at NPF events was mostly correlated with local precipitation or precipitation along the trajectories within 1 day. These results suggest that differences of the number–size distribution and occasions of NPF events among sea areas most closely accord with precipitation along the trajectories. Highlights: Aerosol number–size distributions were observed over the North and South Pacific. Distributions over respective areas were parameterized using lognormal fitting. Bimodal distributions of larger peaks were observed over the eastern equator. New particle formation occurred often at eastern South Pacific mid-latitudes.